Antecedents affecting employee service recovery performance in five star hotel - Tan, Ai Ling *; Kashif Hussain,; Murali, Sambasivan (Australian Academy of Business and Social Sciences, 2014)
Studies on service recovery have been dominated by the investigation on customer’s perceived value after service recovery in the past. However, not many have taken concerted efforts in examining the possible factors that influencing employees’ service recovery performance (SRP). This study examines the role of organizational’s characteristics (reward system, guest focus and commitment, system, policy and procedures of recovery) and employees’ characteristics (organizational’s commitment and prejudgment towards customer’s complaint) on employees’ service recovery performance (SRP) in Malaysia luxury hotels. The finding shows that rewarding system and prejudgement towards complaints has positive influences on employees’ service recovery performance. The result *is contradicting with the findings from past research in which prejudgement towards complainers has adversely affect employees’ service recovery performance.